2015
DOI: 10.2217/fon.15.144
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Prognostic Assessment for Diffuse Large B-Cell Lymphoma

Abstract: Current standard of care therapy for diffuse large B-cell lymphoma (DLBCL) cures a majority of patients with additional benefit in salvage therapy and autologous stem cell transplant for patients who relapse. The next generation of prognostic models for DLBCL aims to more accurately stratify patients for novel therapies and risk-adapted treatment strategies. This review discusses the significance of host genetic and tumor genomic alterations seen in DLBCL, clinical and epidemiologic factors, and how each can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…These studies have demonstrated the great level of heterogeneity characterizing the genetic landscape of DLBCL and prompted further investigation. The identification of clinically relevant biomarkers can form the basis for the development of new drugs, aid clinicians in choosing the appropriate therapies and establishing reliable prognostic models (208)(209)(210).…”
Section: Next-generation Sequencing Of Dlbclmentioning
confidence: 99%
“…These studies have demonstrated the great level of heterogeneity characterizing the genetic landscape of DLBCL and prompted further investigation. The identification of clinically relevant biomarkers can form the basis for the development of new drugs, aid clinicians in choosing the appropriate therapies and establishing reliable prognostic models (208)(209)(210).…”
Section: Next-generation Sequencing Of Dlbclmentioning
confidence: 99%
“…11 Centroblastic lymphoma is the most common subtype with better prognosis compared with immunoblastic and anaplastic variants of DLBCL. 12 A case of diffuse large B-cell lymphoma of the mandible in an 18-year-old male patient is reported.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Of these patients, 60% will receive first line chemoimmunotherapy and be successfully treated. 3 5 The remaining will experience relapsed or refractory (r/r) disease and require subsequent therapy. Standard therapy for r/r DLBCL is salvage chemotherapy followed by high-dose therapy and autologous stem-cell transplantation (SCT).…”
mentioning
confidence: 99%